Perkembangan Profitabilitas Bank BUMN Berdasarkan Struktur Keuangan dan Kinerja Operasional - Nadya Desti Amilya Putri; Bara Zaretta; Dian Prawitasari; Rudi Kurniawan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Based on operational performance and financial structure, this study looks at how Indonesian state-owned banks have become more profitable. The study examines the impact of Debt to Asset Ratio, Firm Size, Non-Interest Income, Credit Risk, and Operating Efficiency on profitability as determined by Return on Assets (ROA) using quarterly data from 2021–2025. Both cross-sectional and time-series fluctuations are captured using a quantitative method with panel data regression. The findings reveal that while Debt to Asset Ratio and Credit Risk do not significantly affect ROA, Firm Size, Non-Interest Income, and Operating Efficiency do. These results imply that operational efficiency, revenue diversification, and scale advantages are more important drivers of profitability development in state-owned banks than leverage structure or credit risk circumstances..